Ideological Aspects of Youth Spirituality Development in the Information Society - Khudaiberganovich, Tashmetov Tukhtasin; qizi, Boliboyeva Tursunoy Sirojiddin (International Journal on Human-Computing Studies, 2023)
As information has become a powerful weapon in global changes, the information communication system is the main factor in the promotion and propaganda of ideological threats on a global scale. With the help of the information communication system, special attention is paid to influence the heart, mind and spirit of people. For this reason, we should not ignore the rise of various ideological and informational attacks. After all, this is the demand of today's times. Only then will we be able to raise a spiritually mature person and a healthy generation in the future.